2013
DOI: 10.4174/jkss.2013.84.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells with p53 deletion detected by fluorescentin situhybridization in peritoneal drainage fluid is correlated with early peritoneal seeding in resectable pancreatic cancer

Abstract: PurposeFree tumor cells in peritoneal fluid in patients with pancreatic cancer may have prognostic significance but there are few reports on methods for the effective detection of free tumor cells. The aims of this study were to identify free cancer cells in peritoneal fluid with fluorescent in situ hybridization (FISH) technique and to investigate its prognostic significance.MethodsTwenty-eight patients with resectable pancreatic cancer who underwent surgical resection were included. Peritoneal washing and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…26 Two studies were assessed as having moderate risk of bias on several domains 27,28 and one study as having moderate to high risk of bias on several domains. 29 It was uncertain whether patients were selected based on a sequential cohort in two studies 27,28 and no exclusion criteria were described in two studies. 27,29 No definition was presented of the secondary outcomes overall survival, disease free survival or peritoneal metastases free survival in two studies.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Two studies were assessed as having moderate risk of bias on several domains 27,28 and one study as having moderate to high risk of bias on several domains. 29 It was uncertain whether patients were selected based on a sequential cohort in two studies 27,28 and no exclusion criteria were described in two studies. 27,29 No definition was presented of the secondary outcomes overall survival, disease free survival or peritoneal metastases free survival in two studies.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…29 It was uncertain whether patients were selected based on a sequential cohort in two studies 27,28 and no exclusion criteria were described in two studies. 27,29 No definition was presented of the secondary outcomes overall survival, disease free survival or peritoneal metastases free survival in two studies. 28,29 No correction was made for confounders in the statistical analysis in three studies [27][28][29] and no information was presented on a possible important confounder, (neo)adjuvant chemo(radiation)therapy, in two studies.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective analysis has demonstrated that a dramatic change in surgical resectability and patient survival occurs as the size of the PC tumor increases from 20 mm to 30 mm [2,3]. Moreover, PC patient survival is dependent on distant metastasis rather than local recurrence, and therefore, early detection and/or prediction of metastasis provide more prognostic relevance than local recurrence [4].…”
Section: Introductionmentioning
confidence: 99%